2004
DOI: 10.1111/j.1461-0248.2003.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically based trait in a dominant tree affects ecosystem processes

Abstract: Fundamental links between genes and ecosystem processes have remained elusive, although they have the potential to place ecosystem sciences within a genetic and evolutionary framework. Utilizing common gardens with cottonwood trees of known genotype, we found that the concentration of condensed tannins is genetically based and is the best predictor of ecosystem-level processes. Condensed tannin inputs from foliage explained 55-65% of the variation in soil net nitrogen (N) mineralization under both field and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
335
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 328 publications
(366 citation statements)
references
References 54 publications
24
335
3
2
Order By: Relevance
“…main effects of N, GT, and Tgr). These results suggest that the genetic and environmental factors that influcened litter traits may also have an effect on decomposition, which would agree with the suggestion of Schweitzer et al (2004) that genetically based variation in plant traits may not only be important for a plant population itself, but may result in important extended phenotypes that could alter ecosystem functioning.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…main effects of N, GT, and Tgr). These results suggest that the genetic and environmental factors that influcened litter traits may also have an effect on decomposition, which would agree with the suggestion of Schweitzer et al (2004) that genetically based variation in plant traits may not only be important for a plant population itself, but may result in important extended phenotypes that could alter ecosystem functioning.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to the differences in leaf traits that occurred in response to N, and among GTs and Tgrs, we also found that leaf and litter values were positively correlated for a number of traits, which agrees with previous studies (King et al 2001;Schweitzer et al 2004). The correlations between leaf and litter values, and the results of the ANOVAs demonstrate that many of the factors that affected some leaf chemistry traits also had significant effects on many of the same litter chemistry traits (i.e.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For example, variation in tannin concentrations can alter leaf litter quality (Lindroth et al, 2002;Madritch et al, 2006). Concentrations of both nitrogen and phenolics (especially tannins) play important roles in litter decomposition and soil nutrient dynamics in forest soils (Schimel et al, 1996;Northup et al, 1998;Hä ttenschwiler and Vitousek, 2000;Kraus et al, 2003;Schweitzer et al 2004). In fact, an alternative hypothesis to the role of tannins as antiherbivore defenses posits that they may be adaptive in their capacity to regulate proximal nutrient cycling (Northup et al, 1998).…”
Section: Discussionmentioning
confidence: 99%